Factores ambientales y su influencia en neumonía en niños menores de 10 años ciudadela Brisas del Río Babahoyo Los Ríos octubre 2018 – abril 2019 - Guayamabe Sánchez, George Farith (2019)
The purpose of the research work is to determine the environmental factors that influence pneumonia in children under 10 years of age; and establish preventive techniques and adequate management of respiratory therapy devices to reduce the risk and prevent infant mortality in homes. In the present study a method of deductive approach was used to verify the process, it was carried out by means of a mixed (qualitative-quantitative) approach, for the review of the background and how environmental factors have influenced the health caused cases of pneumonia in children under 10 years. Also, through statistical processes, they will help with detailed information to grant the validity of this study. In field research, the environmental factors affecting pneumonia were known, seeing that one of the drawbacks is due to a lack of economic resources, little control over continuous medical care and scarce information obtained from the disease. the people in charge of the health area, therefore, the state must help in conjunction with the students of the University by providing free training to combat pneumonia in the country.